1984
DOI: 10.3109/00952998409002657
|View full text |Cite
|
Sign up to set email alerts
|

The Psychiatrically Severe Drug Abuse Patient: Methadone Maintenance or Therapeutic Community?

Abstract: The present research was conducted to examine the effects of pretreatment psychiatric status and treatment duration on improvement following drug abuse rehabilitation. Percent improvement from admission to 6-month follow-up was measured on three criteria: drug use, employment, and criminality. Analyses of the total samples in both the Therapeutic Community (TC) and Methadone Maintenance (MM) programs indicated some quantitative differences between the two modalities but all measures showed a strong and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 14 publications
2
11
0
3
Order By: Relevance
“…Those with depression at 12 months had spent an average of 50 fewer days in treatment for heroin dependence than those without depression. This is consistent with the general observation that a longer treatment duration corresponds to more favorable treatment outcomes, whether it be for drug use the programs were designed to treat or for more peripheral outcomes such as criminality and employment Gossop et al, 1999;Hubbard et al, 1997;McLellan et al, 1984;Simpson, 1981). More specifically, lower levels of depression have been shown to accompany longer stays in treatment (DeLeon et al, 1973;Rounsaville et al, 1982).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Those with depression at 12 months had spent an average of 50 fewer days in treatment for heroin dependence than those without depression. This is consistent with the general observation that a longer treatment duration corresponds to more favorable treatment outcomes, whether it be for drug use the programs were designed to treat or for more peripheral outcomes such as criminality and employment Gossop et al, 1999;Hubbard et al, 1997;McLellan et al, 1984;Simpson, 1981). More specifically, lower levels of depression have been shown to accompany longer stays in treatment (DeLeon et al, 1973;Rounsaville et al, 1982).…”
Section: Discussionsupporting
confidence: 82%
“…Longer treatment durations have consistently been associated with more favorable treatment outcomes in terms of drug use, criminality, and employment Gossop, Marsden, Stewart, & Treacy, 1999;Hubbard, Craddock, Flynn, Anderson, & Etheridge, 1997;McLellan, Childress, Griffith, & Woody, 1984;Sanchez-Carbonell, Cami, & Brigos, 1988;Simpson, 1981). In contrast, individuals who have undertaken more treatment episodes (reflecting less treatment stability) tend to demonstrate poorer treatment outcome (Anglin, Hser, & Grella, 1997;Darke et al, 2005;Gossop et al, 1999;Hser, Grella, Hseih, Anglin, & Brown, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…This domain also entered into the regression equation predicting counseling attendance (or lack thereof). These results are consistent with previous studies that demonstrated that patients rated high in psychological/psychiatric severity levels show poorer treatment outcomes than patients rated lower on this dimension (31,32).…”
Section: Discussionsupporting
confidence: 95%
“…In addition to their manifestation of addiction, adult opiate addicts are disproportionately more likely than never-addicted persons to experience serious mental health problems and personality disorders (Anglin & Hser, 1990;Khantzian & Treece, 1985;Kosten et al, 1985;McLellan et al, 1983McLellan et al, , 1984. It has been found that addicts with severe psychological problems tend to have less favourable drug abuse treatment outcomes than addicts who do not exhibit such problems (McLellan et al, 1983(McLellan et al, , 1984, and are more likely to relapse to opiate drug addiction and criminal activity following treatment (Nurco et al, 1994). Finally, there is evidence that within the United States, white opiate addicts tend to manifest significantly higher levels of psychopathology than addicts from other ethnic groups (Kosten et al, 1985;Shaffer et al, 1982Shaffer et al, , 1988.…”
Section: Introductionmentioning
confidence: 98%